1995
DOI: 10.1111/j.1600-0897.1995.tb00919.x
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Patients With Recurrent Spontaneous Abortion Is Deficient in Transforming Growth Factor β‐2‐Producing “Suppressor Cells” in Uterine Tissue Near the Placental Attachment Site

Abstract: Suppressor cell deficiency is compatible with a role for rejection and/or trophoblast failure in some patients with recurrent miscarriage. Presence of suppressor cells in most patients with missed abortion (4/5) is compatible with an alternative cause of fetal death, similar to findings reported in genetic fetal death mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 34 publications
(7 reference statements)
1
35
0
Order By: Relevance
“…More specifically, we demonstrated that exposure of normal endometrial tissues to TCDD prevents the progesterone-associated increase in TGF-ß 2 . Because TGF-ß 2 is critical to maintaining normal pregnancy and preventing maternal rejection of the fetus [55,56] interfering with the production of this growth factor may have broad implications to reproductive processes other than endometriosis. However, this growth factor plays a central role in progesterone-mediated suppression of MMPs, including the ability of progesterone to prevent experimental endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we demonstrated that exposure of normal endometrial tissues to TCDD prevents the progesterone-associated increase in TGF-ß 2 . Because TGF-ß 2 is critical to maintaining normal pregnancy and preventing maternal rejection of the fetus [55,56] interfering with the production of this growth factor may have broad implications to reproductive processes other than endometriosis. However, this growth factor plays a central role in progesterone-mediated suppression of MMPs, including the ability of progesterone to prevent experimental endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, progesterone-induced expression of TGF-ß 2 is also critical to maintain an appropriate endometrial environment during pregnancy. For example, a subset of women with recurrent spontaneous abortion were found to be deficient in decidua-associated TGF-ß 2 expression [55]. Interestingly, human studies and studies in nonhuman primates indicate that TCDD exposure increases spontaneous abortion [39,40], a uterine event that may be linked mechanistically to the development of endometriosis [41,46].…”
Section: Tcdd As a Disruptor Of Progesterone Actionmentioning
confidence: 99%
“…On the other hand, the role of the other isoforms of TGF␤ is still poorly understood. Because TGF␤2-like molecules are released by CD56ϩ natural killer cells and act as an immunosuppressive factor, implication of TGF␤2 in a local immune reaction preventing rejection of allograft has been suggested (Clark et al, 1994;Lea et al, 1995). This may be the case for TGF␤2 expressed by extravillous cytotrophoblast.…”
Section: Figurementioning
confidence: 99%
“…On the other hand, progesterone has been shown to promote the development of a Th2 response, via an immunomodulatory protein known as progesteroneinduced blocking factor, which inhibits several Th1-type responses in vitro [47,48]. If there is a lack of suppression at the maternofetal interface, due to reduced levels of TGF-b2, a Th1 shift may be induced [49].…”
Section: T-helper 1 Versus T-helper 2 Responsementioning
confidence: 99%